Rose-Colored Answers: Neuropsychological Deficits and Patient-Reported Outcomes after Stroke - Anna M. Barrett (Behavioural Neurology)
Patient-reported, subjective outcomes are promoted as a standard for ethical, valid studies in many neurological disorders. Such outcomes are considered potentially more sensitive and specific to important therapeutic effects, and may be more linked to disability and disease-related life losses than conventional assessments of impairment (e.g. ability to walk, performance on language tests, serological or radiological indices). Self-report is invaluable to identify social and emotional consequences of brain injury: depression, changes in intimate and family relationships, social role and community participation losses. However, common stroke-related neuropsychological deficits are likely to confound subjective stroke outcome measures. The scientific community focused on stroke-related health outcomes may arrive at significantly underestimated patient reports of stroke-related disability, caused by a failure to adjust for the effect on self-report of spatial neglect, deficits of magnitude estimation, pathologic alteration of self-awareness, and alteration in distributed cortical systems supporting emotional semantics and abstraction.